Biochemical composition and yield of new Ukrainian varieties of persimmon - L. M. Shevchuk; O. G. Hrabovetska; Y. Y. Vintskovska; V. O. Tonkha; R. I. Grynyk (Regulatory Mechanisms in Biosystems, 2025)
Global warming is prompting significant changes and improvements in fruit-growing technologies. This is why many heat-loving crops are being cultivated in regions with a temperate continental climate . Breeders are developing frost- and winter-hardy varieties of subtropical crops, including persimmons, that are suitable for growing in different regions of Ukraine. Currently, two persimmon varieties are recommended for cultivation across Ukraine's various natural and climatic zones, but many more have been developed. One of the tasks of scientists is to study the adapt a bility of new varieties, as well as the commercial and consumer quality of their fruit. Research conducted at the Inst i tute of Horticulture of the National Academy of Agrarian Sciences of Ukraine aimed to study the quality indicators of two new Ukrainian persimmon varieties, Agrarna and Stepova Krasunia, which can withstand short-term temperature drops of minus 22–24 °C. These varieties are also resistant to disease and pest damage. We examined the weight, size, and shape of the fruit, as well as their nutrient and biologically active substance content. Trees of the Agrarna variety yield 69.7–71.3 kg per tree, with fruit weighing 153.0–164.4 g. Trees of the Stepova Krasunia variety yield 94.0–87.0 kg per tree, with fruit weighing 171.6–182.7 g. When ripe, Agrarna's skin and flesh turn orange, while those of Ste p naya K rasunia turn red-orange.